(untitled) - Stamatoudi, Irini A. (Cambridge, UK,New York, 2002)
Multimedia products have become highly successful. Yet they are often inadequately protected by existing national and international copyright schemes. This study is one of the first comprehensive, comparative analyses of multimedia works and copyright protection. Stamatoudi considers the nature of the multimedia work, and existing legislation, as well as collections and compilations, databases, audiovisual works and computer programs. Finally, she offers a model for a European legislative solution. Her work will interest academics and students, as well as lawyers and copyright policy makers
Keywords: Copyright,Copyright,Copyright and electronic data processing.,Intellectual property,Luật sở hữu trí tuệ; Interactive multimedia,Audio-visual materials